Aplikasi Android E-Tourism Kuala Tungkal - Rendhika Aditya; Yance Sonatha; Aldo Erianda (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2020)
This research aims to create an Android-based E-Tourism application which aims to make it easier for the public to find important locations around the city of Kuala Tungkal where this application will be able to recommend the place being sought based on the closest distance from the user. In this final project, the android application is made using the Android Studio with the Java programming language. And the API is made using PHP. While in the database section using MySQL. At the end of this final project, the android application will be able to display the location and location details and can sort the location from the closest distance from the user standing